Pemanfaatan MATLAB Untuk Optimalisasi Penelitian Teknik Dan Sains Bagi Dosen Kopertip Indonesia - Ryan Hamonangan; Umi Hayati; Achmad Luthfi; Ahmad Haekal Susanto (CV. Multi Kreasi Media, 2024)
Optimizing the use of MATLAB in engineering and science research is an important aspect for lecturers in improving the efficiency and effectiveness of data analysis and numerical modeling. MATLAB is a numerical computing-based software that has various functions in data processing, numerical analysis, and simulation of complex systems. This study aims to evaluate the level of utilization of MATLAB by Kopertip Indonesia lecturers and identify the challenges faced in its implementation. The methods used in this study include surveys and interviews with lecturers who have used MATLAB in their research. The results show that most lecturers understand the potential of MATLAB in improving the accuracy of their research, but there are obstacles such as lack of training, license limitations, and complexity in advanced programming. Therefore, continuous training and the provision of adequate resources are needed to optimize the utilization of MATLAB. With the increased use of MATLAB in engineering and science research, it is expected to improve the quality of academic research and scientific publications produced by Kopertip Indonesia lecturers.